Molecular detection of Euphorbia yellow mosaic virus infecting chili pepper - De, Aricléia (Tropical Plant Pathology, 2020)
Begomoviruses (family Geminiviridae, genus Begomovirus) are responsible for considerable losses in several tropical crops, more commonly in bean and tomato. Begomoviruses comprise the most numerous and economically destructive group within Geminiviridae. Characteristic symptoms of begomovirus infection in Capsicum chinense (chili pepper, Solanaceae) were observed in smallholder farms in the state of Amazonas. The molecular detection and identification of begomoviruses affecting chili pepper were conducted from symptomatic foliar samples collected at 14 farms in the municipalities of Presidente Figueiredo, Iranduba and Manaus (Amazonas state). Begomovirus was detected in five out of the 69 samples, all of the cultivar Lupita. Pairwise sequence comparisons and phylogenetic analysis based on the complete sequence of the DNA-A component identified the isolates as members of the species Euphorbia yellow mosaic virus (EuYMV). Comparative analysis with 36 EuYMV isolates grouped the Amazonian isolates in a single clade, indicating a low degree of genetic variability for this begomovirus. © 2020, Sociedade Brasileira de Fitopatologia.